Encouraging Employee Innovative Behavior in the Public Sector through Effective Leadership Styles: A Systematic Review - Makhrojan, Roni; Sudiro, Achmad; Thoyib, Armanu (Universitas Padjadjaran, 2025)
The innovative behavior of employees in the public sector is one of the essential aspects of efforts to improve the quality of public services. Leadership is a key factor that performs a significant role in encouraging public sector employees to engage in innovation activities. This research aims to explore leadership styles and characteristics that can facilitate employees' innovative behavior in public organizations. The study was carried out using a systematic literature review approach with the PRISMA framework. A total of 48 scientific articles were selected for in-depth review and analysis. The results of the analysis show that the transformational leadership style is the approach most widely discussed in the public sector context and is proven to be effective in encouraging employee innovative behavior. A deeper analysis found that leadership characteristics such as supporting innovation and creativity, inspiration and motivation, collaboration and empowerment, visionary thinking, and building good personal relationships were found to be closely related to the innovative behavior of organizational members. These findings make a significant contribution to the development of leadership literature in the public sector while offering practical guidance for public organizations in implementing effective leadership strategies to encourage innovation.